The automatic millionaire : a powerful one step plan to live and finish rich - Bach, David (Penguin Books, 2004)
Outlines a system for achieving financial security and building wealth, discussing how to make the most out of automated financial transactions, including 401ks, scheduled transfers, and early-payoff programs.